Narirutin Mitigates Dextran Sodium Sulfate-Induced Enteritis in Procambarus clarkii by Modulating Intestinal Microbiota - Jian Li; Yitian Chen; Yanping Cai; Huiling Zhang; Bin Qiu; Xingfei Huang; Yan Wen; Aimin Wang; Bin He; Yude Wang; Shaojun Liu (Fishes, 2026)
Enteritis is a disease that affects Procambarus clarkii, significantly impacting aquaculture due to its high incidence and mortality rates, resulting in economic losses. Currently, the molecular mechanisms behind enteritis in Procambarus clarkii are not well understood. In this study, we established a model of intestinal inflammation induced by dextran sodium sulfate (DSS). Subsequently, histopathological changes, transcriptome analysis, intestinal microbiota analysis and immunofluorescence analysis were conducted. Histopathology showed that after treatment in the DSS + Narirutin (NR) group, there was an improvement in intestinal inflammation, and the structure of the intestinal tissue was partially restored. The intestinal transcriptome analysis revealed that in the DSS + NR group, 234 genes were upregulated and 188 genes were downregulated after treatment. This indicates a significant change in gene expression. KEGG enrichment analysis revealed that the DEGs were significantly enriched in TGF-β signaling pathway and PI3K-Akt signaling pathway. The results from 16S rRNA sequencing showed that in the DSS + NR group, the relative abundance of Akkermansia muciniphila significantly increased. Immunofluorescence results showed that, compared to the control group, the expressions of Occludin, nuclear factor-kB-p65 (NfkB-p65), Zonula occludens-1 (ZO-1), and Claudin-1 decreased following DSS treatment. However, treatment with NR was able to inhibit these changes. This further validated that NR can alleviate enteritis in Procambarus clarkii.